PENGARUH PERENCANAAN KARIR DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KOMITMEN KARYAWAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG TELUK KUANTAN - Gusnita, Nidya; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine the effect of Career Planning and Leadership toJob Satisfaction and Employee Commitment at PT. Bank Rakyat Indonesia (Persero)Tbk Branch of Teluk kuantan. Population of this research is all employees PT.Bank Rakyat Indonesia (Persero) Tbk Branch of Teluk kuantan which amounts 251people with a total sample of 197 people. The analysis tool used is path analysis usingSPSS version 21. The results of study show (1) Career planning has a positive andsignificant impact to employee commitment (2) Career planning has a positive andsignificant impact to employee commitment through job satisfaction (3) Leadership hasa positive and significant impact to employee commitment (4) Leadership has a positiveand significant to employee commitment through job satisfaction (5) Job satisfactionhas a positive and significant impact to employee commitment. The result of study haveimplication to career planning and leadership at PT Bank Rakyat Indonesia (Persero)Tbk branch of Teluk Kuantan which need to be improved in order to increase jobsatisfaction and if job satisfaction is high, it will increase employee commitment forcompany.